Utilization of the Local Potential Campus Area as a Learning Resource Related to Morphology-Based Poaceae Diversity - Yudhistian Yudhistian; Imas Cintamulya (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
The utilization of local potential in the campus area has not been done optimally. The need for contextualized learning resources requires lecturers to provide appropriate learning resources for students, including biology education students in plant morphology. This study aims to utilize the local potential of the campus area as a learning resource regarding the diversity of Poaceae based on morphological reviews. The type of research used is descriptive quantitative. The data collection method in this study was observation. Sampling technique by making plots with the quadrat method with a size of 1x1 meter at several points in the campus area. The results of this study indicate that the Poaceae family identified in the PGRI Ronggolawe University campus area consists of 12 species, including Stenotaphrum secundatum, Elymus repens, Poa annua, Paspalum dilatatum, Chloris barbata, Zoysia japonica, Muhlenbergia schreberi, Thyrsotachys oliveri, Bambusa vulgaris, Cymbopogon citratus, Digitaria sanguinalis, Panicum repens with four subfamilies namely Bambusoideae, Pooideae, Panicoideae, Chloridoideae with a total of 259 individuals found. Overall, the level of Poaceae diversity in the campus area is H’ = 2.19, which is a moderate category. The level of Poaceae diversity in the campus area from the highest to the lowest value is the subfamily Panicoideae (1.09), Chloridoideae (1.05), Pooideae (0.69), and Bambusoideae (0.66). Analysis of the potential of the research results shows that the diversity of Poaceae in the campus area can be used as learning material for plant morphology for biology education students.